2000
DOI: 10.1097/00005537-200001000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Quality of Life in Vestibular Schwannoma Patients Measured by the SF36 Health Questionnaire

Abstract: Objective: To quantify the postoperative quality of life in patients following surgical treatment for vestibular schwannoma. Study Design: Patient self. assessment using the short form 36 (SF36) multidimensional quality of life health questionnaire. Sexand age-matched normalized scores were calculated using a standardized process and accepted normative data. Setting: Tertiary referral skull base unit. Results: An 80o/ o response rate (90 patie nts) was achieved. The postoperative quality of life in vestibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 23 publications
8
77
1
7
Order By: Relevance
“…2,3,7,19,22,31 Our findings and those of Sandooram et al 26 and Di Miao et al 8 are at some variance with the findings of these studies. However, it must be pointed out that in our study we compared the QOL at follow-up with preoperative QOL, whereas in the retrospective studies, the only comparison possible was with values obtained in the general population.…”
Section: Improvement In Qol After Surgerysupporting
confidence: 74%
See 2 more Smart Citations
“…2,3,7,19,22,31 Our findings and those of Sandooram et al 26 and Di Miao et al 8 are at some variance with the findings of these studies. However, it must be pointed out that in our study we compared the QOL at follow-up with preoperative QOL, whereas in the retrospective studies, the only comparison possible was with values obtained in the general population.…”
Section: Improvement In Qol After Surgerysupporting
confidence: 74%
“…1,6,13,26 Similarly, while some reports showed women to have lower scores than men, 2,14,19,20,22,31 other studies, including our own, showed no difference in SF-36 scores between male and female patients. 1,6,7 Tumor Size Several authors have reported no effect of tumor size on QOL scores. 1,6,7,23 However, others have reported a worse QOL in patients with larger tumors.…”
Section: Age and Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…This would have provided a more holistic view of each patient and taken into account other aspects of living such as pain, headache, facial symptoms, sleep, concentration, memory, activities of daily living, and work. 14,17,19 Another potential problem with the present study was the choice of questionnaires. All three questionnaires were normed using populations of symptomatic patients.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in patients with conditions of varying etiology, pure tone audiometry has been shown to correlate only weakly with disability, 10,11 tinnitus intensity does not correlate with tinnitus handicap, 12 and there is no relationship between vestibular test results and dizziness handicap. 13 Although there have been several papers considering handicap, disability, and quality of life experienced by VS patients [14][15][16][17][18][19][20][21][22] these have all concentrated on the patient's condition postoperatively. The authors are unaware of any studies looking at preoperative handicap.…”
mentioning
confidence: 99%